2011
DOI: 10.7589/0090-3558-47.4.936
|View full text |Cite
|
Sign up to set email alerts
|

The Pied Crow (Corvus Albus) Is Insensitive to Diclofenac at Concentrations Present in Carrion

Abstract: ABSTRACT:Diclofenac, a nonsteroidal anti-inflammatory drug (NSAID), kills vultures (Gyps spp.) that consume tainted carcasses. As a result, vulture populations in India, Nepal, and Pakistan have been devastated. Studies on meloxicam and ketoprofen demonstrated that the toxicity of the NSAIDs is unpredictable, thereby necessitating individual testing of all available NSAIDs. Because it is no longer practical to use vultures for toxicity testing, we evaluated the Pied Crow (Corvus albus) as a model. Pied Crows (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
(28 reference statements)
0
10
2
1
Order By: Relevance
“…Previous studies demonstrated that sensitivity differences in response to NSAIDs exist between avian species . For example, one report determined that although chickens can succumb to diclofenac toxicity (50% lethal dose ~10 mg/kg), they are more tolerant of the biochemical effects (abnormal renal parameters and acute renal tubular necrosis) compared to Gyps vultures (50% lethal dose ~0.1 mg/kg) .…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Previous studies demonstrated that sensitivity differences in response to NSAIDs exist between avian species . For example, one report determined that although chickens can succumb to diclofenac toxicity (50% lethal dose ~10 mg/kg), they are more tolerant of the biochemical effects (abnormal renal parameters and acute renal tubular necrosis) compared to Gyps vultures (50% lethal dose ~0.1 mg/kg) .…”
Section: Discussioncontrasting
confidence: 52%
“…Biochemical or fatal changes of diclofenac‐treated birds in previous studies occurred at doses ranging from 0.005 mg/kg to 20 mg/kg with Gyps vultures being the most sensitive to effects . Of the studies that utilized chickens, a 2 mg/kg dose caused biochemical, but nonlethal, changes .…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Além das desordens metabólicas nutricionais e consequentes patologias renais sendo incriminadas como causas da gota úrica (Poffers et al 2002, Herbert et al 2011, o diclofenaco e derivados também tem sido incriminado como causador desta patologia, devido à contaminação ambiental por estes fármacos, levando a altos índices de mortalidade de rapinantes de vida livre (Muralidharan & Dhananjayan 2010, Naidoo et al 2011, Harris 2013, o que devemos estar atento, uma vez que estas drogas estão sendo amplamente utilizadas na medicina veterinária.…”
Section: Discussionunclassified
“…The choice of this species was twofold, firstly the easier availability to the study site, as well as being less endangered than the Indian vulture species. From this controlled acute toxicity study, the Cape Griffon vulture was shown to be equally susceptible to diclofenac as the oriental white-backed vulture at 0. , and a mean residence time of 15.11 + 4.13 h. To evaluate the importance of the pharmacokinetic profile obtained, Naidoo et al [61] compared it to those published for other bird species (figure 2). This included the African white-backed vulture (Gyps africanus), the pied crow (Corvus albus), the turkey vulture (Cathartes aura) and the domestic chicken (Gallus domesticus).…”
Section: In Vivo Approaches In Studying Comparative Metabolismmentioning
confidence: 99%